Keadilan Kompensasi dan Pengakuan Karyawan dengan Mediasi Komitmen Organisasi pada Pengembangan Reputasi Merek - Idawati, Rd Nurvitasari; Alirejo, M Subroto (Awatara Publisher, 2026)
This study examines how compensation fairness and employee recognition influence brand reputation development through organizational commitment among MSMEs in Purwakarta. Using a quantitative survey of 372 employees and PLS-SEM analysis, the results indicate that compensation fairness and employee recognition both exert significant positive effects on organizational commitment. Organizational commitment, in turn, has a strong positive impact on brand reputation development, confirming its central mediating role. The indirect effects of compensation fairness and employee recognition on brand reputation through commitment are also statistically significant, demonstrating that internal reward perceptions translate into external brand outcomes via employees’ psychological attachment. These findings highlight that material and symbolic rewards operate as complementary mechanisms in shaping employee loyalty and brand-supportive behavior. From a theoretical perspective, the study extends fairness-based explanations by integrating organizational commitment as a key process linking human resource practices to branding consequences. Practically, the results suggest that MSMEs can strengthen their reputation by ensuring transparent and equitable compensation while simultaneously institutionalizing simple but consistent recognition practices. Such strategies are particularly relevant in resource-constrained contexts where formal branding investments are limited. Overall, the study emphasizes that sustainable brand reputation begins with internal justice and acknowledgment for local MSMEs.